Exploring teachers’ conceptions of assessment: A quantitative study in a secondary school setting - Mat Yusoff, Shahazwan; Abdul Razak, Rafiza; Chin, Hai Leng; Marzaini, Anwar Farhan (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2023)
This study aims to unveil the conceptions of assessment held by secondary school teachers, which have a significant impact on their classroom assessment practices and students’ study habits. The four variables that underpin the conceptions of assessment in this study are improvement, school accountability, student accountability, and irrelevance. The research was conducted in a single district of Selangor, with the participation of 80 secondary school teachers. Descriptive findings reveal that the conception of improvement garnered the highest level of agreement among participants, while school accountability received the lowest level of agreement. Furthermore, a MANOVA analysis was employed to investigate the potential influence of gender and years of teaching experience on participants’ perceptions. The analysis demonstrates that neither gender nor years of teaching experience significantly affect participants’ conceptions of assessment. This study’s outcomes are expected to provide valuable insights to all education stakeholders, particularly those concerned with secondary school assessment practices, regarding teachers’ conceptions of assessment.